Seeding solutions: Closing the ruminant feed gap through forage innovation in Southeast Asia - Burkart, Stefan; Mwendia, Solomon; Karimi, Peggy; Atieno, Mary; Dao, Hang Thi; Philp, Joshua (American Society of Agronomy, 2025)
Southeast Asia faces a significant and growing ruminant feed deficit, constraining the development of sustainable livestock systems amidst rising demand for animal‐sourced foods. This article analyzes the scale of the deficit and the role improved cultivated forage systems can play in closing it across five countries: Vietnam, Cambodia, Timor‐Leste, Laos, and Thailand. The analysis estimates that closing the feed gap over a period of 10 years will require the establishment of more than 314,000 ha of cultivated forage and the participation of over 400,000 adopting farmers. This highlights the untapped potential of forage seed systems, with a projected regional seed market value of up to $163 million over 10 years, alongside $1.6 billion in forage crop value under a gradual adoption scenario. However, achieving this scale requires overcoming systemic barriers, including weak seed markets, limited private sector engagement, fragmented policy implementation, and poor farmer access to quality planting materials. Forage development is therefore both a technical and institutional challenge, calling for farmer training, improved extension services, access to finance, embedding forage seed systems into national strategies, decentralizing seed production, harmonizing regional seed regulations, and incentivizing private sector engagement. With the right investments and policy frameworks, improved forage systems can enhance livestock productivity, strengthen rural livelihoods, and contribute to food security and climate resilience across Southeast Asia.